2023
DOI: 10.1002/anie.202303561
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Synthesis of a Highly Stable Aluminium Phosphonate Metal–Organic Framework Showing Reversible HCl Adsorption

Abstract: A concept for obtaining isoreticular compounds with tri-instead of tetravalent metal cations using highly acidic reaction conditions was developed and successfully applied in a high throughput study using N,N'-piperazinebis(methylenephosphonic acid) (H 4 PMP), that resulted in the discovery of a new porous aluminium phosphonate denoted CAU-60•6 HCl. The high-throughput study was subsequently extended to other trivalent metal ions. Al-CAU-60•6 HCl demonstrates reversible desorption of HCl (18.3 wt % loading) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…An attractive complementary approach would be a technique that combines the superior safety profile of hydrochloric acid with the advantageous reactivity and electrochemical properties of gaseous hydrogen chloride. Although ionic liquids ( 23 25 ) and metal-organic frameworks ( 26 ) for the reversible absorption of HCl are reported, none of them were used as scalable storages that can directly be used for hydrochlorination reactions and electrolysis. Recently, Geng and coworkers ( 27 ) demonstrated that imidazole-based deep eutectic solvents can be used for the efficient coupling of HCl capture and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive complementary approach would be a technique that combines the superior safety profile of hydrochloric acid with the advantageous reactivity and electrochemical properties of gaseous hydrogen chloride. Although ionic liquids ( 23 25 ) and metal-organic frameworks ( 26 ) for the reversible absorption of HCl are reported, none of them were used as scalable storages that can directly be used for hydrochlorination reactions and electrolysis. Recently, Geng and coworkers ( 27 ) demonstrated that imidazole-based deep eutectic solvents can be used for the efficient coupling of HCl capture and conversion.…”
Section: Introductionmentioning
confidence: 99%
“…The tail group may be an inert capping group or a reactive part, which can govern the surface wettability of the modified substrate. Phosphonic acids have been widely utilized in the surface-science due to its ease of synthesis and intensive coordination with metal oxides. , Moreover, the electron structure and surface wettability of modified metal oxides can be precisely adjusted by tail groups of phosphonic acids, such as −OH and −NH 2 . Therefore, employing phosphonic acid to adjust and balance the wettability of carbon-supported molybdenum oxide and gaining a deeper insight into the relationship between the local reaction environment and activity would initiate a new era for the design of ODS catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…By introducing a hydroxy group in the ortho position of the sulfonate group, −OH and sulfonate O atoms can coordinate with Ti 4+ ions in a chelating manner, thereby enhancing the stability of the framework. The formation of a titanium-phenol functional motif further promotes visible light absorption via LMCT. compared with H 4 DOBDC, the strong acidity of H 4 DOBSC may provide more acid medium to stabilize Ti 4+ ions, which facilitates the growth of single crystals. , …”
mentioning
confidence: 99%
“…compared with H 4 DOBDC, the strong acidity of H 4 DOBSC may provide more acid medium to stabilize Ti 4+ ions, which facilitates the growth of single crystals. , …”
mentioning
confidence: 99%
See 1 more Smart Citation